2012
DOI: 10.1038/ncomms2088
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone determines the start of the sensitive period of imprinting and primes later learning

Abstract: Filial imprinting in precocial birds is the process of forming a social attachment during a sensitive or critical period, restricted to the first few days after hatching. Imprinting is considered to be part of early learning to aid the survival of juveniles by securing maternal care. Here we show that the thyroid hormone 3,5,3′-triiodothyronine (T3) determines the start of the sensitive period. Imprinting training in chicks causes rapid inflow of T3, converted from circulating plasma thyroxine by Dio2, type 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(138 citation statements)
references
References 46 publications
2
135
1
Order By: Relevance
“…Recent data suggest that, instead, the thyroid hormone T(3) is responsible for the opening of the sensitive period for the formation of the imprinting memory of an artificial object (e.g., Yamaguchi et al, 2012). Also pharmacological elevation of glutamate levels extends the imprinting period, indicating the role of glutamate receptors (Parsons and Rogers, 1997).…”
Section: Developmental Origins Of the General Predispositions For Animentioning
confidence: 96%
“…Recent data suggest that, instead, the thyroid hormone T(3) is responsible for the opening of the sensitive period for the formation of the imprinting memory of an artificial object (e.g., Yamaguchi et al, 2012). Also pharmacological elevation of glutamate levels extends the imprinting period, indicating the role of glutamate receptors (Parsons and Rogers, 1997).…”
Section: Developmental Origins Of the General Predispositions For Animentioning
confidence: 96%
“…In the brain of sockeye salmon, the mRNA encoding the TRH precursor has been studied via in situ hybridization [28], and the expression of cDNA encoding TRH receptor subtypes has been examined [29]. Recently, it was reported that T 3 determines the onset of the sensitive period for imprinting, and that it plays a critical role in later learning in chicks Gallus gallus domesticus [30]. Although the onset of downstream migration, including smoltification, is under the complex regulation of several endocrine hormones, the brain-pituitary-thyroid (BPT) axis should have a critical role in imprinting during downstream migration.…”
Section: Imprinting Migrationmentioning
confidence: 99%
“…NMDA is involved in the development of neural networks, learning, and memory in chicks [66]. Thyroid hormone determines the onset of the sensitive period for imprinting and plays a critical role in later learning [30]. A trial experiment has been conducted to improve the olfactory imprinting capability of juvenile masu salmon through the oral administration of these three bioactive substances, T 4 , DHA, and NMDA, and the subsequent evaluation of the gene expression levels of NMDA receptor essential subunit NR1 and TRHa/b genes.…”
Section: Improvement Of the Olfactory Imprinting Capabilitymentioning
confidence: 99%
“…In the brain of sockeye salmon, the mRNA encoding the TRH precursor has been studied via in situ hybridization , and the expression of cDNA encoding TRH receptor subtypes has been examined (Saito et al 2011). It was reported that T3 determines the onset of the sensitive period for imprinting and that it plays a critical role in later learning in chicks (Gallus gallus domesticus) (Yamaguchi et al 2012). Although the onset of downstream migration, including smoltification, is under the complex regulation of several endocrine hormones, the BPT axis is considered to play critical roles in imprinting during downstream migration.…”
Section: -1 Hormone Profiles Of Juvenile Chum Salmon During Imprintmentioning
confidence: 99%